Czym jest „zabawa” w literaturze religijnej XVII i XVIII wieku? Rekonensans genologiczny - Prabucki, Krzysztof (Zagadnienia Rodzajów Literackich, 2024)
The subject of this article is the problem of the presence of the phenomenon called quasi-genre in the history of literature. The point of departure for such considerations is an article by Antoni Czyż entitled Zabawa barokowa: okruchy genologiczne, published in “Pamiętnik Literacki” in 1984. A discussion with Czyż’s position is undertaken — according to the researcher, a quasi-genre is such a form which represents a “bottom-up system” opposed to the elite products of the literary culture of the time. A reconnaissance was carried out on the meaning of the word “zabawa” in the reality and cultural consciousness of the time. As the most representative works in this trend were written within the circle of religious and devotional literature, a significant part of the exemplary material is of this kind. The criterion for selection was the functioning of the given collection in the readership circulation and the occurrence of the word “zabawa” itself in the title of the work. Discursive statements by the authors or publishers, usually published in the introductions to the individual works, were also compared on a comparative basis. In addition to its polemical ambitions, the study also has the benefit of organising the concepts operating in the state of research. The identification of source material proposed in this study is a preliminary to making future theoretical-literary and genological clarifications.